Effect of Stimulants on Biogenic Methane Formation and Dynamics of Bacterial Population - Pingkan Aditiawati; Agus Pujobroto; Indra Rudiansyah; Harry Rahmadi (Journal of Mathematical and Fundamental Sciences, 2013)
Coal bed methane (CBM) is a renewable energy source produced through thermogenic and biogenic activity during the coal formation process. The aim of this research was to stimulate biogenic methane formation using simple carbon as stimulant. The microcosm set-up was done using subbituminous coal at 37°C in an anaerobic chamber. Stimulation with Na-acetate, methanol, formic acid, and no additions, respectively, was carried out for 54 days; observation took place on day 2, 15, 24, 45, and54. The results of all treatments showed differences in the initial pH of the basal medium: 7.76 (Na-acetate), 6.69 (methanol), 4.06 (formic acid), and 8.95 (no stimultant), respectively. Addition of Na-acetate resulted in the highest methane formation rate (5.034 mmol/g coal on day 24 of incubation), followed by methanol (4.377 mmol/g on day 24 of incubation), formic acid (2.520 mmol/g on day 22 of incubation), and no addition (1.2 mmol/g on day 15 of incubation). Using denatured gradient gel electrophoresis (DGGE) it was observed that the microbial population dynamics of the microcosm depended on the stimulant. A decrease of bands indicated that the addition of Na-acetate and methanol had caused a decrease of bacterial diversity during the stimulation process compared to the control treatment (without stimulant).